Glutaredoxin 1 Deficiency Leads to Microneme Protein-Mediated Growth Defects in Neospora caninum - Song, Xingju; Yang, Xu; Xue, Yangfei; Yang, Congshan; Wu, Kaijian; Liu, Jing; Liu, Qun (Frontiers in Microbiology, 2020)
Neospora caninum is an obligate intracellular protozoan parasite that infects a wide range of mammalian species and causes spontaneous abortion in cattle. N. caninum is exposed to oxidative stress during its life cycle. Oxidoreductase is crucial for parasite response to the environmental stresses. Glutaredoxins (Grxs) are small oxidoreductases of the thioredoxin family proteins that catalyze thiol-disulfide exchange reactions by utilizing electrons from the tripeptide glutathione (γGlu-Cys-Gly; GSH). Grxs are key elements in redox signaling and cell signal transduction. However, Grxs are an unexplored set of oxidoreductases in N. caninum. Here, we identified two cytoplasm located glutaredoxin domain-containing proteins (NcGrx1 and NcGrx3) in N. caninum. To better understand the functions of these Grx proteins, we generated NcGrx1 and NcGrx3 deficiency and overexpression strains. The deletion or overexpression of NcGrx3 had no significant effect on the growth of N. caninum in vitro and in vivo. NcGrx1 knockout parasites displayed a significant growth defect, which was due to the influence on invasion and egress abilities. Moreover, NcGrx1 deficiency decreased the ratio of reduced glutathione (GSH) to oxidized glutathione (GSSG) (GSH/GSSG ratio), caused a significant accumulation of hydroxyl radical in parasites, and an increase in apoptotic cells under oxidative stress (H2O2) condition. To determine the cause of growth defects in ΔNcGrx1, we examined the transcription levels of various invasion-egress related genes as measured by qPCR. We found a significant decrease in MIC1, MIC4, and MIC6 genes. Further investigation found that the secretion of MIC1, MIC4, and MIC6 proteins was significantly affected. Collectively, Ncgrx1 is important for microneme protein-mediated parasite growth, and maybe a potential intervention target for the N. caninum.